DEVELOPMENT OF A POCKET BOOK (ARABIC-ENGLISHINDONESIAN) TO IMPROVE SPEAKING SKILLS AT MADRASAH ALIYAH BAHRUL ULUM MALANG (International Conference on Social and Islamic Studies, 2021)
This pocket book (Arabic-English-Indonesian) was developed for students of MadrasahAliyah class X. The development of this book was carried out as a solution, because thereare still few textbooks that focus on maharah kalam that are applicable and can be directlyapplied in everyday life. In addition, some of the exercises in the textbook do not matchthe skills learned. The large and colorless book size makes students feel bored and boredwhile studying. The objectives of this research are (1) to develop a pocket book (Arabic English-Indonesian) to improve speaking skills.(2)To find out the effectiveness of the books that have been developed and applied to class X Madrasah Aliyah Bahrul Ulum Malang students.This research uses Borgand Gall Research and Development (R&D) research which has been modified from ten steps into six main steps, namely, (1) Needs analysis,(2) Planning,(3) Product development,(4) Validation of material experts and media, (5) Revision, (6) Field trial, and produce the final product. (1) This book consist sof six main materials with the development of themes related to daily activities and isequipped with pictures of conversations that are adapted to the themes being studied, andthere is a quick response code (QR-Code) which contains videos of interesting conversational practices. The design of this book is made in color and not too big, sostudents can easily carry it and can use it. Wherever and whenever. Instruments of data collection were obtained through interviews with Arabic teachers, field observations conducted by researchers, and questionnaires given to students. As a research sample, theresearcher tested the validity of the book to the tenth grade students of Madrasah Aliyah Bahrul Ulum Malang. (2) Based on the average assessment results from the material validation test with the presentation of the material validation results 92%, while for media validation 73% and learning practitioners 92%. The results of the assessment show thatthis book is valid for learning maharah kalam for class X Madrasah Aliyah.